Teaching Strategies in English Classes During the Onsite Transition Period in SMA NEGERI 1 RENDANG - Putu Bagus Suryawan Arijaya; Luh Putu Artini; Ni Luh Gede Eka Wahyuni (Linguistic, English Education and Art (LEEA) Journal, 2023)
After learning activities entered the transition period, the English teachers had to readjust their teaching strategies. Adjustments to teaching strategies must be made to meet students' needs and adjust to the learning curriculum. The purpose of this research is to describe the teaching strategies used by English teachers at SMA Negeri 1 Rendang during the transition period in the field. This study uses a qualitative research paradigm, with two English teachers from SMA Negeri 1 Rendang as research subjects. This study collected data through class observations and interviews using observation sheets and semi-structured interview guidelines. The data analysis procedure was carried out by analysing the results of class observations and interviews with respondents regarding the implementation of learning strategies during the transition period. The results of this study indicate the teaching strategies used by teachers during the transition period. Keywords: teaching strategies, transition period, onsite learning, English teacher